Systematic Review and Meta-analysis: Short-Chain Fatty Acid Characterization in Patients With Inflammatory Bowel Disease. Issue 11 (9th September 2019) - Zhuang, Xiaojun; Li, Tong; Li, Manying; Huang, Shanshan; Qiu, Yun; Feng, Rui; Zhang, Shenghong; Chen, Minhu; Xiong, Lishou; Zeng, Zhirong
Abstract: Background: Alterations in gut microbiota and short-chain fatty acids (SCFAs) have been reported in inflammatory bowel disease (IBD), but the results are conflicting. The aim of this study was to perform a meta-analysis to explore the characterization of SCFAs in IBD patients and their potential role in the occurrence and development of IBD. Methods: Case–control studies investigating SCFAs in IBD patients were identified from several English databases. The standardized mean difference (SMD) with 95% confidence interval (CI) was calculated using the random-effects model. Results: The SMDs of acetate, valerate, and total SCFAs in ulcerative colitis (UC) patients were –0.51 (95% CI, –0.90 to –0.13), –0.65 (95% CI, –1.02 to –0.28), and –0.51 (95% CI, –0.95 to –0.07), respectively. The SMDs of acetate, propionate, and butyrate in patients with active UC were –1.74 (95% CI, –3.15 to –0.33), –2.42 (95% CI, –4.24 to –0.60), and –1.99 (95% CI, –3.39 to –0.60), respectively. However, the SMD of butyrate in UC patients in remission was 0.72 (95% CI, 0.34 to 1.11). In addition, the SMDs of acetate, butyrate, and valerate in Crohn's disease (CD) patients were –1.43 (95% CI, –2.81 to –0.04), –0.77 (95% CI, –1.39 to –0.14), and –0.75 (95% CI, –1.47 to –0.02), respectively. Finally, the SMDs of acetate, propionate, butyrate, valerate, and lactate in IBD patients were –2.19 (95% CI, –3.98 to –0.39), –1.64 (95% CI, –3.02 to –0.25), –1.98 (95% CI, –3.93 to –0.03), –0.55 (95% CI, –0.93 to –0.18), and 4.02 (95% CI, 1.44 to 6.61), respectively. Conclusions: There were alterations of SCFAs in IBD patients, and inconsistent SCFA alterations were found in CD and UC. More importantly, inverse SCFA alterations existed in patients with active UC and those in remission. Abstract : There were alterations of SCFAs in IBD patients, and inconsistent SCFA alterations were found in CD and UC. More importantly, inverse SCFA alterations in UC patients with different disease statuses were found in our subgroup analysis. However, SCFAs were not significantly different between UC patients with proctosigmoiditis and those with pancolitis.